Viet Cong at Wounded Knee : the trail of a Blackfeet activist - Kipp, Woody (American Indian lives., 2004)
It was at Wounded Knee, huddled under a night sky lit by military flares and the searchlights of armored carriers seeking him out, that Vietnam vet Woody Kipp realized that he, as an American Indian, had become the enemy, the Viet Cong, to a country that he had defended with his life. With candor, bitter humor, and biting insight, this book tells the story of the long and tortuous trail that led Kipp from the Blackfeet Reservation of his birth to a terrible moment of reckoning on the plains of South Dakota. Kipp's is a story of Native values and practices uneasily crossed with cowboy culture, teenage angst, and quintessentially American temptations and excesses.